2022
DOI: 10.1101/2022.01.17.22269409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clonal hematopoiesis and risk of chronic liver disease

Abstract: Chronic liver disease is a major public health burden worldwide. Despite various liver injury mechanisms, progression of chronic liver disease follows a common pathway of liver inflammation, injury and fibrosis. We examined the association between clonal hematopoiesis of indeterminate potential (CHIP) and chronic liver disease in 58,358 individuals from four prospective cohorts with whole exome sequencing data (Framingham Heart Study, Atherosclerosis Risk in Communities Study, UK Biobank and Mass General Brigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…DNA methylation is one of the essential epigenetic regulations, and aberrant changes in DNA methylation are associated with various pathological diseases, such as cancer [61], obesity [62], and inflammatory autoimmune disorders [63]. Liver regeneration after PHx is also affected by epigenetic regulation in liver disease [29,64,65]. Previous studies have found that Tet2 demethylase mainly transforms 5mc to 5hmc in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is one of the essential epigenetic regulations, and aberrant changes in DNA methylation are associated with various pathological diseases, such as cancer [61], obesity [62], and inflammatory autoimmune disorders [63]. Liver regeneration after PHx is also affected by epigenetic regulation in liver disease [29,64,65]. Previous studies have found that Tet2 demethylase mainly transforms 5mc to 5hmc in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that Tet2 demethylase mainly transforms 5mc to 5hmc in the nucleus. Mice transplanted with Tet2-deficient hematopoietic cells showed high levels of inflammatory cytokines in macrophages [65]. Our study investigated whether TET2 in macrophages affects liver regeneration through inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of hematopoietic stem cells, driver mutations in genes with diverse functions, including DNA methylation (DNMT3A, TET2) 4,5 , RNA splicing (SF3B1, U2AF1) 6 , chromatin remodeling (ASXL1) 7 , and DNA damage response (TP53, PPM1D) [8][9][10] can lead to a clonal expansion of hematopoietic stem cells termed clonal hematopoiesis of indeterminate potential (CHIP) when such mutations make up >4% of peripheral blood cells (variant allele fraction, VAF≥2%). CHIP is the pre-cancerous precursor lesion for myeloid hematologic malignancy [11][12][13] , but numerous studies in human and model systems have linked CHIP to diverse diseases of aging, including coronary artery disease 14,15 , stroke 16 , heart failure 17 , chronic obstructive pulmonary disease 18 , osteoporosis 19 , and chronic liver disease 20 . However, CHIP is less commonly observed among patients with Alzheimer's disease 21 .…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition to myeloid neoplasms, CH has also been associated with an increased risk of all-cause mortality and with nonhematological illnesses such as cardiovascular diseases, liver disease, solid cancers, chronic obstructive pulmonary disease, and gout. 1,2,[5][6][7][8][9][10][11] In some instances, the disease risk may be mediated by abnormal mature cell progeny (eg, macrophages) of the CH clone, 7 but in others the basis of the association is not clear. 5 The somatic mutations responsible for CH affect a selected set of genes previously identified as drivers of myeloid malignancies, including those coding for epigenetic regulators DNMT3A and TET2; the chromatin regulator ASXL1; splicing factors such as SF3B1, SRSF2, and U2AF1; DNA damage response proteins such as TP53 and PPM1D; and regulators of growth signaling, such as JAK2, GNAS, CBL, and GNB1.…”
mentioning
confidence: 99%
“…lonal hematopoiesis (CH), the clonal expansion of a hematopoietic stem cell (HSC) and its progeny driven by somatic mutations, is a common phenomenon that becomes progressively more prevalent with age to affect the majority of people aged 70 years or older. [1][2][3][4] CH is associated with increased risks of hematological cancers 1 and several nonhematological diseases, [5][6][7][8][9][10][11] such that an improved understanding of its pathobiology can help manage or prevent some of these consequences. However, despite a flourishing interest in CH, our understanding of how somatic mutations impart an HSC with enhanced fitness to drive clonal expansion remains very limited.…”
mentioning
confidence: 99%